Assessment of SARS-CoV-2 Seropositivity During the First and Second Viral Waves in 2020 and 2021 Among Canadian Adults - Xuyang Tang; Abha Sharma; Maria Pasic; Patrick Brown; Karen Colwill; Hellen Gelband; H.C. Birnboim; Nico Nagelkerke; Isaac I. Bogoch; Aiyush Bansal; Leslie Newcombe; Justin Slater; et al. (2022)
The incidence of infection during SARS-CoV-2 viral waves, the factors associated with infection, and the durability of antibody responses to infection among Canadian adults remain undocumented.